Memórias de trabalhadores do Vital Brazil: um diálogo entre a saúde e a comunidade - Sousa, Rosa Gouvêa de (2009)
This study objective was to identify references that indicate the meaning of gathering and continuity in the community of the 'Morro do Vital Brazil'. This community, as this study intended to point out, would rise by the mid twentieth century in the Instituto de Hygiene, Sorotherapia e Veterinária do Estado do Rio de Janeiro surroundings, nowadays known as the Instituto Vital Brazil. Owing to be a pharmaceutical factory, its production would need workers who, in this particular case, have started to live over the hill behind the Institute, but still inside its territory. There, a community flourished with characteristics like cooperation, union and collective. As the factory has prospered, the number of residents increased and started a collective of houses and families sharing several aspects in common. This sense of identity had made possible meeting with the government politicians and policies, like the Programa Médico de Família, Niterói ́s primary health care program. The relationship born with this program in particular became the initial interest of this research, due to its researcher is a family doctor in the health center located in that area and the way her patients behave that indicated an unique intimacy and position of speech to this health program. Therefore, this study identifies characteristics of that community and the other elements around which contributed to the creation of this gathering and the methodology was oral history.